Erfüllung und Reichweite zivilrechtlicher Offenlegungsansprüche Eine Untersuchung der Regeln über den Zugang zu Beweismitteln im europäischen und US-amerikanischen Recht - Hechler, Jonathan (Studien zum Zivilrecht, 2023)
The author examines how a party in need of evidence can gain access to evidence and information that is in the hands of its opponent. In this respect, on the one hand, the claims to information, accounting and disclosure of evidence, which are already known in German law, are examined. On the other hand, it will be shown how in other legal systems access to such means of evidence is an elementary part of civil proceedings. On this basis, a concept is developed by means of which the legal practitioner can develop appropriate answers on a familiar basis to questions concerning the fulfillment of claims granting access to evidence.